Fatty Acid–Binding Protein 4 (FABP4) Is Associated with Cartilage Thickness in End-Stage Knee Osteoarthritis. (December 2021) - Schadler, Paul; Lohberger, Birgit; Thauerer, Bettina; Faschingbauer, Martin; Kullich, Werner; Stradner, Martin Helmut; Husic, Rusmir; Leithner, Andreas; Steinecker-Frohnwieser, Bibiane
Background: There is no single blood biomarker for the staging of knee osteoarthritis (KOA). The purpose of this study was to assess the relationship of obesity, serum biomarkers, the hip-knee-ankle angle (HKAA) with sonographic cartilage thickness. Methods: We conducted a cross-sectional study of n = 33 patients undergoing knee arthroplasty. Body mass index (BMI) was recorded, and patients were grouped based on BMI. Serum blood samples were collected, and the following biomarkers were measured using the ELISA technique (subgroup of n = 23): oxidized low-density lipoprotein (oxLDL), soluble receptor for advanced glycation end-products (sRAGE), fatty acid–binding protein 4 (FABP4), membrane-bound phospholipase A2 (PLA2G2A). The HKAA was analyzed on full-length limb standing x-ray images. Cartilage thickness was assessed on ultrasound images. Multivariable regression analysis was performed to account for confounding. Results: After adjusting for age, gender, and HKAA, obese patients had thicker medial femoral cartilage (β = 0.165, P = 0.041). Furthermore, lateral cartilage thickness was negatively correlated with FABP4 level after adjusting for of age, gender, BMI, and HKAA (β = −0.006, P = 0.001). Confirming previous studies, after adjustment, FABP4 level was associated with a higher BMI group (β = 42.99, P < 0.001). None of the other markers (oxLDL, PLA2G2A, and sRAGE) was associated with BMI or cartilage thickness. Discussion: Our results indicate that BMI has a weak, positive association with cartilage thickness in end-stage KOA patients. FABP4 levels were negatively associated with cartilage thickness. While our study is limited by a small sample size, these results further highlight the role of FABP4 as promising biomarkers of burden of disease in KOA.